Health: Hospital Medical Waste Management Laws that Does Not Comply with Environmental Quality Standards - Feliciani Palmita Sari Harapan; Andika Persada Putera (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research is conducted to analyze the regulation of medical waste management and the legal consequences of medical waste management in hospitals that do not meet environmental quality standards related to health aspects. This research method is descriptive which will produce an overview of medical waste management regulations relating to health and environmental aspects. This research is normative in nature. The approach used is a statutory approach which is carried out by examining all regulations related to the legal issues addressed. Furthermore, the conceptual approach is derived from the views and doctrines developed in legal science. while the analysis method used is qualitative analysis method. The results of the study show that there are at least two laws that regulate medical waste, namely the Health Law and the Environmental Management Law. Medical waste management is very important, because medical waste that is not managed properly will have a very negative impact on the environment which will have an impact on human health.